Eradication of methicillin-resistant Staphylococcus aureus with an antiseptic soap and nasal mupirocin among colonized patients - an open uncontrolled clinical trial - Kampf Günter; Kramer Axel (BMC, 2004)
Abstract Background Aim of the study was to determine the clinical efficacy of a new antiseptic liquid soap (Stellisept® scrub), based on the combination of undecylenamidopropyltrimonium methosulphate (4%) and phenoxyethanol (2%), for eradication of MRSA among colonized patients who do not receive antibiotic therapy. Methods Over two years 50 MRSA patients in 6 hospitals were observed. Treatment was defined as the daily application of Stellisept scrub for the antiseptic body and hair wash (at least 60 s) in combination with nasal mupirocin. A treatment cycle was a minimum of 5 days treatment. Screening was carried out at least 48 h after the treatment cycle was finished, with 24 h between each of the requested three or more samplings, which included the nasopharynx, groin, axilla, perineum and other MRSA-positive skin areas. Results Fifteen cases were retrospectively excluded (lack of outcome documentation, concomitant antibiotic therapy, open wounds). All 35 patients had colonization with MRSA before antiseptic treatment on the skin, in the groin (80%), the axilla (25.7%), the perineum (20%) or other skin areas (14.3%). Colonization at more than one skin sites was found in 34.3%. Nasal colonization was found in 21 of 28 patients (75%), 7 patients were without nasal screening prior to the antiseptic treatment. After one treatment cycle MRSA was eradicated in 25 patients (71.4%), after a second cycle the total eradication rate was 91.4%, after a third cycle the rate increased to 94.2%. No patient discontinued the antiseptic treatment due to dermal intolerance of the product. Conclusions Progressive eradication of MRSA carriage was observed with the antiseptic soap and mupirocin. The eradication rate was not biased by concomitant antibiotic treatment, screening during treatment or lack of evidence for colonization in contrast to other studies with other preparations.